1997
DOI: 10.1128/jb.179.18.5802-5811.1997
|View full text |Cite
|
Sign up to set email alerts
|

A promoter for the first nine genes of the Escherichia coli mra cluster of cell division and cell envelope biosynthesis genes, including ftsI and ftsW

Abstract: We constructed a null allele of the ftsI gene encoding penicillin-binding protein 3 of Escherichia coli. It caused blockage of septation and loss of viability when expression of an extrachromosomal copy of ftsI was repressed, providing a final proof that ftsI is an essential cell division gene. In order to complement this null allele, the ftsI gene cloned on a single-copy mini-F plasmid required a region 1.9 kb upstream, which was found to contain a promoter sequence that could direct expression of a promoterl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 60 publications
2
73
0
Order By: Relevance
“…Therefore, it can be concluded that ftsI is mainly cotranscribed along with the mraZ, mraW, ftsL and murE genes of the operon probably from the Pmra promoter, as described in E. coli and B. subtilis (Hara et al, 1997), and probably also from a minor promoter (PftsI) as in B. subtilis (Daniel et al, 1996). This result also suggests that the second GTG (at position 2 293 165) most probably is the start codon of ftsI.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Therefore, it can be concluded that ftsI is mainly cotranscribed along with the mraZ, mraW, ftsL and murE genes of the operon probably from the Pmra promoter, as described in E. coli and B. subtilis (Hara et al, 1997), and probably also from a minor promoter (PftsI) as in B. subtilis (Daniel et al, 1996). This result also suggests that the second GTG (at position 2 293 165) most probably is the start codon of ftsI.…”
Section: Resultssupporting
confidence: 55%
“…Our results suggest that ftsI is transcribed both from a minor promoter (PftsI), as in B. subtilis (Daniel et al, 1996), and also as a part of the polycistronic mraZ, mraW, ftsL and murE transcript from an upstream promoter (Pmra), as described for E. coli and B. subtilis (Hara et al, 1997;Mengin-Lecreulx et al, 1998). The ftsI gene seems to be essential for the viability of C. glutamicum since gene disruption was possible only in the merodiploid strain C. glutamicum MAPF.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A weak promoter within the ftsQ gene, pA, was reported by Yi et al (1985) and by Flärdh et al (1997), using transcriptional fusions, although the corresponding RNA species was not detected by S1 mapping (Aldea et al, 1990). Evidence was presented that suggested that promoters upstream of pQ2 are necessary to achieve sufficient ftsZ expression for cell viability (Dai and Lutkenhaus, 1991), but recent results have made this possibility unlikely (Hara et al, 1997). To test whether ppGpp affected ftsQAZ expression at an untested promoter or at the post-transcriptional level, we assayed the concentration of FtsZ protein in wild-type cells and in two mecillinam-resistant mutants, argS201 and a p lac -relAЈ-bearing strain, both of which have a twofold higher ppGpp concentration (Joseleau-Petit et al, 1994).…”
Section: Discussionmentioning
confidence: 96%
“…The E. coli K-12 derivative strains and the plasmids used are listed in Table 1. The rcsA::cam allele, in which the chloramphenicol resistance (cam) gene of pACYC184 was inserted into the EcoRV site within the rcsA gene, was first constructed on the plasmid pHR704, which carries the 4.4-kb BamHI fragment of l clone 344 of the Kohara miniset library (Kohara et al, 1987) containing rcsA, and then crossed into the chromosome as described (Hara et al, 1997).…”
Section: Methodsmentioning
confidence: 99%